Pemodelan Kasus Penyakit Difteri dI Provinsi Jawa Timur Menggunakan Pendekatan Regresi Spasial - Suciptawati, Ni Luh Putu; Susilawati, Made; Hendarta, Hellena (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2024)
Diphtheria is a disease that is easily transmitted, caused by a bacterium called Corynebacterium Diphtheria which attacks the respiratory tract so that sufferers experience difficulty breathing and can cause death. This research aims to model the factors method which is suspected of influencing diphtheria cases in East Java Province using spatial regression The data used is secondary data obtained from publications East Java Province Health Profile 2018 and publications from the Central Agency East Java Statistics (BPS). The results showed that the best model obtained was Spatial Error Model (SEM) with AIC=286,16 dan R2=55,98%. Variabels that significantly influence diphtheria in East Java province in 2018 are: population aged 10 years and over with junior high school education, the number of DPT-HB immunizations, and the percentage of poor people